Rola Kościoła w europejskim kryzysie pokoju według Josepha Ratzingera - Pogoda-Kołodziejak, Adriana (Collectanea Theologica, 2018)
Is modern Europe just a mental idea? Is it, as the moral force after World War II, the power of reconciling nations, and of establishing and creating peace? In the understanding of the Church, peace does not reduce itself to the mere absence of war, but such a state is recognized as an essential element in forming positive relations between countries and creating social structures within them. Cardinal Joseph Ratzinger assigns to Christians certain tasks thanks to which world peace can be preserved. The Church ought to instil the habit of defending it by exhibiting values which stand up to war and violence, the most important of which is love towards fellow human beings. Man has to sensitize himself to God in order to feel the power of conscience, which will allow him to create good law in society.